1972
DOI: 10.1002/jbm.820060404
|View full text |Cite
|
Sign up to set email alerts
|

Environmental fatigue testing of silastic finger joint prostheses

Abstract: SummaryHeat vulcanized silicone elastomer (Silastic-Dow) has been in clinical use as a prosthetic replacement material for over a decade. When subjected to operating stress in body fluids, as in cardiac poppet-valves, failure has occurred. Fractures of silastic finger-joint prosthesis have also been experienced.Chemical and fractographic analyses of such failed finger-joint prostheses raise the suspicion of fatigue failure. Severe discoloration of the implant at the point of maximal stress concentration, the p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
10
0

Year Published

1973
1973
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 36 publications
(11 citation statements)
references
References 4 publications
(3 reference statements)
1
10
0
Order By: Relevance
“…The application of this theory to the flexible joint implant was discounted by a 1973 study indicating an insignificant amount of lipid transfer between the joint fluid and the implant. That study also showed no correlation between the small amount of lipid transfer and the frequency of implant fracture (11,12).…”
Section: Vcotmentioning
confidence: 93%
“…The application of this theory to the flexible joint implant was discounted by a 1973 study indicating an insignificant amount of lipid transfer between the joint fluid and the implant. That study also showed no correlation between the small amount of lipid transfer and the frequency of implant fracture (11,12).…”
Section: Vcotmentioning
confidence: 93%
“…To test this hypothesis we attempted to duplicate the constraint in our machine, as shown schematically in Fig.7. T h e prosthesis still lasted lo7 cycles without failure (19), but the discoloration at the point of severest bending was now quite intense, almost as much as the prostheses which had failed in use. Since the locations of the discolored regions suggest that mechanical stress aids the absorption of lipids, and the crazed or roughened surfaces could serve as fracture initiators (following the corrosion fatigue analogy), it was decided to remove the prostheses for examination, the results of which we now report below.…”
Section: Silastic Finger Joint Prosthesismentioning
confidence: 98%
“…Weightman et al 4 reported that discoloration of silicone rubber as a result of lipid absorption is accelerated by flexural stresses. The yellowing of the implant hypothetically was attributed to the lipid absorption.…”
mentioning
confidence: 98%
“…[1][2][3][4][5][6] The mechanism of degradation of the silicone elastomer material in the finger joints is addressed incompletely in the literature.…”
mentioning
confidence: 99%